2013
DOI: 10.1371/journal.pone.0056471
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characterization of 3-(2-amino-ethyl)-5-[3-(4-butoxyl-phenyl)-propylidene]-thiazolidine-2,4-dione (K145) as a Selective Sphingosine Kinase-2 Inhibitor and Anticancer Agent

Abstract: In our effort to develop selective sphingosine kinase-2 (SphK2) inhibitors as pharmacological tools, a thiazolidine-2,4-dione analogue, 3-(2-amino-ethyl)-5-[3-(4-butoxyl-phenyl)-propylidene]-thiazolidine-2,4-dione (K145), was synthesized and biologically characterized. Biochemical assay results indicate that K145 is a selective SphK2 inhibitor. Molecular modeling studies also support this notion. In vitro studies using human leukemia U937 cells demonstrated that K145 accumulates in U937 cells, suppresses the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 55 publications
(93 reference statements)
6
84
0
Order By: Relevance
“…4C ), which is in excellent agreement with previous reports ( 20 ). We also examined the effect of the SphK2-specifi c inhibitor K145 ( 21 ). As can be seen in Fig.…”
Section: Fluorescence Assays In 384-well Plate Format For Sphk Inhibisupporting
confidence: 91%
See 1 more Smart Citation
“…4C ), which is in excellent agreement with previous reports ( 20 ). We also examined the effect of the SphK2-specifi c inhibitor K145 ( 21 ). As can be seen in Fig.…”
Section: Fluorescence Assays In 384-well Plate Format For Sphk Inhibisupporting
confidence: 91%
“…As can be seen in Fig. 4D , K145 suppressed SphK2 activity with an IC 50 of 33.7 µM, which is slightly higher than the K i value determined with the conventional radioactive assay ( 21 ). Taken together, these results suggest that our new fl uorescence method is suitable for rapid screening of SphK1 and SphK2 inhibitors.…”
Section: Fluorescence Assays In 384-well Plate Format For Sphk Inhibimentioning
confidence: 63%
“…Recently, sphingolipid metabolism was shown to be required for activation of BAK and BAX and apoptosis induction (38). However, recent studies have demonstrated a role for SK2 in tumor promotion (11,35) and demonstrated that inhibition of SK2 can inhibit the in vitro and in vivo growth of the myeloid leukemia cell line, U937 (39). We examined the effects of Sphk2 deletion in the development of BCR/ABL-driven ALL, and SK2 inhibition in ALL cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…by guest, on www.jlr.org Downloaded from as xenograft growth of tumor cells in mice (34,35). Studies with FTY720, a S1P mimetic prodrug, have also served to demonstrate the role of S1P.…”
Section: S1p a Lipid Mediatormentioning
confidence: 99%